2007
DOI: 10.1021/jp0649347
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution 15N NMR of the 225 K Phase Transition of Ammonia Borane (NH3BH3):  Mixed Order-Disorder and Displacive Behavior

Abstract: We report high resolution 15N NMR probing of the solid-solid phase transition of 15N-labeled ammonia borane (NH3BH3) at 225 K. Both the 15N isotropic chemical shift (delta iso) and the spin-lattice relaxation rate (T1-1) exhibited strong anomalies around 225 K. The analysis of T1-1 using the Bloembergen, Purcell, and Pound model showed that the motional correlation time, tau, increased from about 1 to 100 ps and the corresponding Arrhenius activation energy increased from 6 to 14.5 kJ/mol on going through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 44 publications
7
53
0
Order By: Relevance
“…Such a transition is typical of second-order phase transformations. Our observations of modulus pre-softening are complementary and coherent with previous NMR results in NH 3 BH 3 [8], and make the above hypothesis of B-N axis dynamics more solid.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such a transition is typical of second-order phase transformations. Our observations of modulus pre-softening are complementary and coherent with previous NMR results in NH 3 BH 3 [8], and make the above hypothesis of B-N axis dynamics more solid.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested [8] that the transition is triggered by the slowing down of the NH 3 motion, but at present the mechanism driving the phase transformation is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this bond is reflected in a series of important papers addressing its inelastic neutron scattering [3] and its 225 K phase transition, studied using high-resolution solidstate 15 N NMR spectroscopy. [4] In addition, the structures of methylamine borane molecules (Me n H 3Àn N:BH 3 , n = 1-3) have been investigated using X-ray diffraction, gas-phase electron diffraction, and quantum chemical calculations. [5] Plumley and Evanseck have discussed the covalent and ionic nature of the dative bond in ammonia borane based on high-level QCISD(T) calculations, [6] and Anane et al have carried out a comparison of the B À N with the B À P bond [7] by comparing H 3 N:BX 3 with H 3 P:BX 3 (X = H, F, Cl) at the G2/MP2 level.…”
Section: Introductionmentioning
confidence: 99%
“…22 At ambient conditions ammonia borane crystallizes in a tetragonal space group I4mm with a unit cell containing two molecules. 23,24 NMR measurements 25,26 revealed that the NH 3 and BH 3 groups undergo motion about the B-N bond. This motion freezes out at low temperature and at about T t = 225 K a first order rotational order-disorder phase transition with a change in structure from body-centered tetragonal ͑bct͒ to orthorhombic ͑space group Pmn2 1 ͒ occurs.…”
Section: Introductionmentioning
confidence: 99%